ECOWAS FREEDOM OF MOBILITY AND ITS NATIONAL SECURITY IMPLICATIONS FOR NIGERIA - Aduloju, Ayodeji; Opanike, Abimbola (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
This study examines the effects of the ECOWAS Free Movement Protocol on national security in Nigeria in the context of a wider regional and global security landscape. From primary data drawn from structured interviews and fieldwork, combined with secondary sources, the research argues that while the Protocol facilitates regional integration and regional trade, at the same time it interacts with Nigeria’s narrow institutional capacity, insecure borders, and corruption and hence amplifies security vulnerabilities. However, blaming insecurity on the porousness of borders in isolation could miss the intricacy of interaction among transnational criminal networks, weak multilateral enforcement institutions, and the inherent gap between the ECOWAS integration vision and domestic enforcement realities. This study employs both functionalism and the regional security complex theory to place Nigeria’s national security issues within the frameworks of regional interdependence and international systemic processes. The findings of the study propose that effective security governance in Nigeria requires not just better management of the borders but also regional coordination and institutional reforms to address both internal and external drivers of insecurity.